2016
DOI: 10.1088/0957-4484/27/17/175706
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Cu doping on the mechanical and optical properties of zinc oxide nanowires synthesized by hydrothermal route

Abstract: Zinc oxide (ZnO) is a wide-bandgap semiconductor material with applications in a variety of fields such as electronics, optoelectronic and solar cells. However, much of these applications demand a reproducible, reliable and controllable synthesis method that takes special care of their functional properties. In this work ZnO and Cu-doped ZnO nanowires are obtained by an optimized hydrothermal method, following the promising results which ZnO nanostructures have shown in the past few years. The morphology of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…ZnO is a wide bandgap (3.4 eV) semiconductor, which has a stable wurtzite structure with lattice spacing a = 0.325 nm and c = 0.521 nm [33,34]. It has attracted intensive research effort for its unique properties such as thermal and chemical stability, optical transparency, and piezoelectricity [35].…”
Section: Introductionmentioning
confidence: 99%
“…ZnO is a wide bandgap (3.4 eV) semiconductor, which has a stable wurtzite structure with lattice spacing a = 0.325 nm and c = 0.521 nm [33,34]. It has attracted intensive research effort for its unique properties such as thermal and chemical stability, optical transparency, and piezoelectricity [35].…”
Section: Introductionmentioning
confidence: 99%
“…48 This result is similar to the UV emission peak from Ni-doped ZnO-NWs. 51 The near bandgap emission maximum of 395 nm in the Cu-MeNTA sample shows is somewhat red-shifted from the Cu-doped ZnO NW in comparison to the un doped structures (385 nm), 52 383 nm for ZnO NW in Pd-MeNTA and similar to Pdnanoparticle-decorated ZnO-NWs and palladium-zinc oxide nanowire nano ber 382 nm. 47,53 Table 3 lists the defect density of the nanowires grown in the various types of MeNTA based on the ratio of NBE to DLE peak intensities (INBE/IDLE).…”
Section: Experimental Methodsmentioning
confidence: 94%
“…Moreover, Si-NPls are quite attractive structures that have shown wider absorption and enhanced performance due to the clear increment of their active surface. 11,12 However, as photoanode, bare Si suffers from fast degradation and corrosion in aqueous environments, which dramatically limits its operation time 13 Several strategies based on the introduction of protective coatings to hinder surface passivation have been proposed to extend the lifetime of Si based photoanodes 14,15 Additional studies have shown the advantages of TiO2 or ZnO coatings on the performance of Si-NPls, [16][17][18] due to their optical tunability, 6 mechanical reinforcement, 10,19 and high photoactive performance. 6,10 Recently, photoactive junctions of precious metals and semiconducting materials have shown enhanced carrier transport capabilities of photogenerated electrons which could provide a more efficient catalytic performance for water splitting [20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%